microRNA-944 overexpression is a biomarker for poor prognosis of advanced cervical cancer - Park, Sunyoung (BMC Cancer, 2019)
BACKGROUND: One-third of cervical cancer patients are still diagnosed at advanced stages. The five-year survival rate is decreased in about 50% of advanced stage cervical cancer patients worldwide, and the clinical outcomes are remarkably varied and difficult to predict. One of the miRNAs known to be associated with cancer tumorigenesis is miR-944. However, the prognostic value of miR-944 in cervical cancer has not been fully investigated. The aim of this study was to analyze clinical significance and prognostic value of miR-944 in cervical cancer. METHODS: The expression levels of miR-944 were detected using quantitative reverse transcription polymerase chain reaction in five types of cervical cancer cell lines and 116 formalin-fixed paraffin-embedded (FFPE) cervical tissues. The association between the expression levels of miR-944 and prognostic value was analyzed using the Kaplan-Meier analysis and Cox proportional hazards model. RESULTS: The expression levels of miR-944 in cervical cancer tissues were significantly higher compared with those in normal tissues (P < 0.0001). Moreover, the expression levels of miR-944 in cervical cancer cell lines and FFPE tissues with human papillomavirus (HPV) infection were significantly higher compared to those without HPV infection (P < 0.01 and P = 0.02). High miR-944 expression was also markedly associated with bulky tumor size (P = 0.026), advanced International Federation of Gynecology and Obstetrics (FIGO) stage (P = 0.042), and lymph node metastasis (P = 0.030). In particular, high miR-944 expression group showed shorter overall survival than the low miR-944 expression group in the advanced FIGO stage (84.4% vs. 44.4%, HR = 4.0, and P = 0.01). CONCLUSIONS: These results suggest that miR-944 may be used as a novel biomarker for improving prognosis and as a potential therapeutic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5620-6) contains supplementary material, which is available to authorized users.